2019
DOI: 10.1002/bies.201900045
|View full text |Cite
|
Sign up to set email alerts
|

Initiated by CREB: Resolving Gene Regulatory Programs in Learning and Memory

Abstract: Consolidation of long‐term memory is a highly and precisely regulated multistep process. The transcription regulator cAMP response element‐binding protein (CREB) plays a key role in initiating memory consolidation. With time processing, first the cofactors are changed and, secondly, CREB gets dispensable. This ultimately changes the expressed gene program to genes required to maintain the memory. Regulation of memory consolidation also requires epigenetic mechanisms and control at the RNA level. At the neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 134 publications
(364 reference statements)
0
17
0
Order By: Relevance
“…CREB has been extensively studied in the brain since it is involved in a variety of relevant processes such as learning and memory or neuronal survival, among others ( Benito and Barco, 2015 ). For example, it is known that CREB activity is crucial for the maintenance of long-term plasticity and memory formation ( Bourtchuladze et al, 1994 ; Bartsch et al, 1998 ; Kaldun and Sprecher, 2019 ). Moreover, the genetic program downstream CREB is complex and different transcriptional programs could be elicited depending on the triggering stimulus, cellular context, and upstream signaling events ( Nonaka et al, 2014 ).…”
Section: Nr4a2 Transcription Factormentioning
confidence: 99%
“…CREB has been extensively studied in the brain since it is involved in a variety of relevant processes such as learning and memory or neuronal survival, among others ( Benito and Barco, 2015 ). For example, it is known that CREB activity is crucial for the maintenance of long-term plasticity and memory formation ( Bourtchuladze et al, 1994 ; Bartsch et al, 1998 ; Kaldun and Sprecher, 2019 ). Moreover, the genetic program downstream CREB is complex and different transcriptional programs could be elicited depending on the triggering stimulus, cellular context, and upstream signaling events ( Nonaka et al, 2014 ).…”
Section: Nr4a2 Transcription Factormentioning
confidence: 99%
“…After analyzing the modulation level of CREB, we further asked which signaling pathways are involved in the observed CREB phosphorylation in the nucleus accumbens during relief learning. Several studies demonstrated that CREB phosphorylation at Ser-133 may occur through any of its upstream protein kinases including protein kinase A (PKA), Ca 2+ -calmodulin-dependent kinases (CaMK), protein kinase B (PKB or Akt) extracellular-Signal-regulated kinase (ERK) or mitogen-activated protein kinase (MAPK) protein kinase C (PKC), p90 ribosomal S6 kinase (p90RSK), casein kinase I, and casein kinase II [12,13,32]. Based on previous studies, NMDAR induction plays a critical role in relief acquisition [9,10] and is able to stimulate CREB activity through different pathways [17,18,33].…”
Section: Discussionmentioning
confidence: 99%
“…A key protein in synaptic plasticity and memory is the cAMP response elementbinding protein (CREB) which functions as a transcriptional activator after its phosphorylation [11]. Previous studies in hippocampus-dependent contextual fear learning showed a biphasic pattern for CREB phosphorylation in long-term memory formation [12][13][14]. In the first phase (within 1 h after conditioning) CREB phosphorylation is likely to be stress-related and can trigger transcription of immediate early genes.…”
Section: Introductionmentioning
confidence: 99%
“…CREB also plays a role in synaptic plasticity and acts as a transcription factor of immediate-early genes (IEGs) related to synaptic plasticity (Kaldun & Sprecher, 2019). Arc is one of these target IEGs;…”
Section: Dopamine Biosynthetic Process 1 Daomentioning
confidence: 99%